2021
DOI: 10.3390/microorganisms9050897
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome of Indonesian Adults Associated with Obesity and Type 2 Diabetes: A Cross-Sectional Study in an Asian City, Yogyakarta

Abstract: Indonesia is a developing country facing the national problem of the growing obesity and diabetes in its population due to recent drastic dietary and lifestyle changes. To understand the link between the gut microbiome, diet, and health of Indonesian people, fecal microbiomes and metabolomes of 75 Indonesian adults in Yogyakarta City, including obese people (n = 21), type 2 diabetes (T2D) patients (n = 25), and the controls (n = 29) were characterized together with their dietary and medical records. Variations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 64 publications
1
14
0
Order By: Relevance
“…Previous sequence data of the gut microbiome in individuals with African and South-Asian genetic backgrounds have already revealed taxa associated with type 2 diabetes in those ethnic groups [ 16 , 17 , 21 , 61 , 70 , 71 , 72 , 73 ]. In Indian subjects, several studies have reported a higher abundance of Escherichia in treated T2D cases and a higher abundance of Lactobacillus in both treated and untreated T2D cases [ 16 , 17 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous sequence data of the gut microbiome in individuals with African and South-Asian genetic backgrounds have already revealed taxa associated with type 2 diabetes in those ethnic groups [ 16 , 17 , 21 , 61 , 70 , 71 , 72 , 73 ]. In Indian subjects, several studies have reported a higher abundance of Escherichia in treated T2D cases and a higher abundance of Lactobacillus in both treated and untreated T2D cases [ 16 , 17 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, Romboutsia was identified as a robust and strong biomarker in the relation between Met-T2D and the gut microbiome in both ethnicities. Besides its potential relation to metformin use [24,61,62], Romboutsia was also previously negatively correlated with the abundance of Enterobacteriaceae, in line with the observed higher abundance of Escherichia/Shigella in Met-T2D cases in our study [63]. As for the other overlapping ASVs, the effect of Met-T2D remained significant on the abundance of Clostridium sensu stricto 1, Peptostreptococcaceae Terrisporobacter and Intestinibacter bartlettii, and Escherichia/Shigella after all adjustments in African Surinamese, while those significant effects vanished in South-Asian Surinamese after adjustment for other medication use (often not addressed in the previous studies).…”
Section: Overlapping Biomarkers Between Ethnicities Were Previously Related To Metformin Usementioning
confidence: 99%
“…To compare the Pakistan gut microbiota with that of other cohorts or populations, we systemically searched for publicly available 16S rRNA gene amplicon (targeting the V3-V4 region) datasets of T2D case-control studies with available metadata or identification of T2D status. Sequences from five published studies were subsequently downloaded from the National Center for Biotechnology Information and the DNA Data Bank of Japan: PRJNA661673 (China), 65 PRJNA766337 (Japan), 66 PRJDB9293 (Indonesia), 67 PRJNA588353 (Sudan), 68 and PRJNA554535 (Pakistan; an independent cohort consisting of participants residing in Islamabad). 15 An endogamous agriculturist Indian cohort of healthy adults (PRJNA399246) was also included, 69 representative of a non-industrialized population from the same geographic region.…”
Section: Methodsmentioning
confidence: 99%
“…A similar phenomenon was found in Indonesian T2D patients. A study by Therdtatha et al found that a T2D group of subjects harboring a high abundance of B. fragilis showed low levels of conjugated BAs, especially TUDCA, the level of which was restored by the administration of metformin [ 18 ].…”
Section: Gut Microbiota Of Asian People Associated With Lifestyle Dis...mentioning
confidence: 99%
“…For instance, a trend toward an increase in consumption of calorie-dense diets by Asian people, such as diets containing refined carbohydrates, fat, red meats, and low fiber contents, has been largely confirmed by several studies [ 13 , 14 , 15 ]. This occasionally distresses the gut microbiota of Asian people, eventually leading to dysfunction of their gut microbial communities [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%